Study the inhibitory effect of pomegranate crusts and tannin on some salmonella species isolated from diarrhea cases in Mosul city - Khuder Suliman; Saba Al-Haleem (College of Education for Pure Sciences, 2019)
The present investigatiorr includecl isolation and cliagnosis of the nricro-organistn Salmonella fi'orrr diarrhoeal cases, Specimens were collected frorn (300) patients during rhe period July 2000- March 2oot. The fbllowirrg serotypes S. typhimurium (55%), S. typhi (20 %) , S. hato (15 %) and S. anatum (10 %) were isolatecl. 'rhe infection was concentrated in age -classes rangirrg r)'onr (2-5) year.s which reached (35oh) and was followed by the class ranging frorn (6- l2) rnonths which slrowed (25%). The aqueous and alcoholic extracts of potrregranate shells showed high inhibitory effect on the selected serotypes of Salmonella. The minimurn inhibitory concentration (MIC) of aqueous extract of porne-eranate shells against the serotype S. 4;pl-ri was (0.1) rng/crn3 and S. rytphimut'ium (0.5) mg/cmr and (0.5) nrg/imr ; (0.0625) mg/cmr for alcoholic extract of pomegranate shells and (0. 125) ; (0.25),rg7.rn, fo. taninis.